Erasing the Thin Blue Line: An Indigenous Proposal - Matthew Fletcher (2021)
My earliest interaction with the police came in September 1976 when I was four.1 My mom, who is Anishinaabe, and dad, who is white, had driven us in our small car all the way up north from southwest Michigan where we lived to take a quick camping trip north of Sault Ste. Marie, Ontario. At the border, the police separated my mother from us and interrogated her about the validity of my that extremely intimidating encounter, the police turned to the rest of us and our vehicle. They removed our suitcases from the car and dumped the contents on the road. They removed the back seat and contents of the glove compartment. They walked dogs through the front and back seats, inspected under the hood, and inspected the vehicle’s undercarriage. After a while, they found nothing incriminating and casually welcomed us into Canada. But they forced us to repack our luggage and put our car back together. And they told us to hurry it up.